If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -9 = -1x + -1(7 + 2x) Reorder the terms: -9 + -2x = -1x + -1(7 + 2x) -9 + -2x = -1x + (7 * -1 + 2x * -1) -9 + -2x = -1x + (-7 + -2x) Reorder the terms: -9 + -2x = -7 + -1x + -2x Combine like terms: -1x + -2x = -3x -9 + -2x = -7 + -3x Solving -9 + -2x = -7 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -9 + -2x + 3x = -7 + -3x + 3x Combine like terms: -2x + 3x = 1x -9 + 1x = -7 + -3x + 3x Combine like terms: -3x + 3x = 0 -9 + 1x = -7 + 0 -9 + 1x = -7 Add '9' to each side of the equation. -9 + 9 + 1x = -7 + 9 Combine like terms: -9 + 9 = 0 0 + 1x = -7 + 9 1x = -7 + 9 Combine like terms: -7 + 9 = 2 1x = 2 Divide each side by '1'. x = 2 Simplifying x = 2
| 7m+7n-7(6m-9m)= | | 3(2x-7)=-18 | | 15y^2-25y^3= | | -6b=57-15 | | (x^2-8)(x^2-8)=0 | | -14x+7=150 | | 12u-10v-7u= | | cos(6x-1)=0 | | 3x+57=90 | | 8x+1=5x+12 | | 6ab-5b^2-5b+6a=0 | | d-9=15 | | -10(10x+1)+10(-9x+3)= | | 6a-4(10+12a)=6(9-7a) | | y+x=18 | | 14v+8+2v=36 | | -7(-6-7x)+3(x-9)= | | (8+y)(8+y)=0 | | -m-7(-8m-4)= | | 10P+4(24-p)=210 | | 4x^2+17x+2x=10 | | 3x-14=7x+7 | | 4y-1+y+31=6y+30-4y | | 4+55x=44x+7 | | -r+24=-4(r-6) | | -9(b-3)+3b= | | 27=a-18 | | -28=4x-2(3x+6) | | (5y+4)(5y-4)=0 | | 3(z-2)+6x-2= | | 5n+11=32 | | 10-2x=x-8 |